Influence of Sea Surface Temperature on Precipitation Anomalies in Northeast China During the Late Summer, 2024: A Statistical Assessment Based on Generalised Equilibrium Feedback Analysis - Yitong Lin; Yihe Fang; Chunyu Zhao; Yu Zhang; Chang Liu; Xinze Li (International Journal of Climatology, 2026)
During the late summer (July–August) of 2024, the Northeast China (NEC) suffered extreme precipitation and severe floods, with rainfall in southern NEC marking the highest recorded since 1985. Using the daily precipitation records from 245 national meteorological stations across the NEC, this study analyses the characteristics of the rainfall anomalies and the associated large‐scale circulation patterns in the late summer of 2024. Based on the generalised equilibrium feedback analysis (GEFA) method, we investigate the response of precipitation and atmospheric circulation anomalies to sea surface temperature (SST) anomalies across various oceanic basins. The results indicate that the NEC precipitation anomalies in the late summer of 2024 exhibit a remarkable response to both the first empirical orthogonal function (EOF) mode of the North Pacific SST (NP1) and the second EOF mode of the tropical Atlantic SST (TA2). The NP1 features widespread positive SST anomalies extending from the Kuroshio Extension to the west coast of North America, and the TA2 is marked by positive anomalies in the northern tropical Atlantic and negative anomalies in the southeastern region. Both modes induce enhanced precipitation over NEC, with anomaly centres located southward, closely matching the observations. Specifically, the positive SST anomalies of the NP1 mode enhance the upward heat flux over the Japan Sea and its eastern regions, inducing positive geopotential height anomalies over Japan, thereby leading to an enhanced and northward anticyclone in the Northwest Pacific. Moreover, for the TA2 mode, the positive SST anomalies in the northern tropical Atlantic are closely associated with the downstream propagating Rossby wave train, resulting in an anomalous circulation pattern characterised by active Northeast China cold vortexes over the NEC and an intensified western Pacific subtropical high. These circulation anomalies facilitate the northward transport of warm and humid airflows to the NEC and promote the frequent convergence of cold and warm airflows over the NEC region, thereby contributing to the anomalously more precipitation over the NEC in the late summer of 2024. By quantifying the relative contributions of different SST modes, this study helps better target key precursors of NEC summer rainfall anomalies, which provides useful guidance for seasonal climate forecasting in NEC.